2020
DOI: 10.1186/s12874-020-01119-3
|View full text |Cite
|
Sign up to set email alerts
|

Social network analysis methods for exploring SARS-CoV-2 contact tracing data

Abstract: Background Contact tracing data of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic is used to estimate basic epidemiological parameters. Contact tracing data could also be potentially used for assessing the heterogeneity of transmission at the individual patient level. Characterization of individuals based on different levels of infectiousness could better inform the contact tracing interventions at field levels. Methods Standard social network analysis methods used for exploring infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
(35 reference statements)
0
26
0
Order By: Relevance
“…Dehghanbanadaki et al (2020), based on Scopus data, concluded that BMJ (Clinical Research Edition) had published the most articles in the field of COVID-19. Nagarajan et al (2020) also believe that SNA helped health practitioners and their activities in investigating the SARS-COV-2. Also, Laksham et al (2020) claimed that reputable Open Access journals had played an important role in publishing the results of Coronavirus research.…”
Section: Discussionmentioning
confidence: 94%
“…Dehghanbanadaki et al (2020), based on Scopus data, concluded that BMJ (Clinical Research Edition) had published the most articles in the field of COVID-19. Nagarajan et al (2020) also believe that SNA helped health practitioners and their activities in investigating the SARS-COV-2. Also, Laksham et al (2020) claimed that reputable Open Access journals had played an important role in publishing the results of Coronavirus research.…”
Section: Discussionmentioning
confidence: 94%
“…Because contact tracing is a time intensive endeavor for HCPs, social network mapping can assist HCPs with having a conversation about a patient’s social circle, who needs to be contacted to limit further spread. Social network mapping can also identify social network members who should be contacted to disseminate SARS-CoV-2 information [ 25 ]. These methods have been successfully employed in previous projects that sought to increase HIV prevention activities, such as condom use and HIV prevention knowledge [ 26 ].…”
Section: Social Network Approach As a Strategy To Overcome Challenges Of Pandemic Tracking Treatment And Acceptance Of Sars-cov-2 Testingmentioning
confidence: 99%
“…Or, briefly, to how social relationships are organized within society [12,13]. In effect, ideas and statistical models from the network science [14] have already been applied to various topics related to the COVID-19 pandemic, such as the global and local spread of the virus [1,15,16], the exploration of SARS-COV-2 contact tracing data [6,17,18], the assessment of vaccination strategies [19,20], the analysis of vaccine patents [21], the evaluation of distancing strategies [22], etc.…”
Section: Introductionmentioning
confidence: 99%